CO-Ar collisions: ab initio model matches experimental spectra at a sub percent level over a wide pressure range. (September 2021) - Serov, E.A.; Stolarczyk, N.; Makarov, D.S.; Vilkov, I.N.; Golubiatnikov, G. Yu.; Balashov, A.A.; Koshelev, M.A.; Wcisło, P.; Thibault, F.; Tretyakov, M. Yu.
Highlights: The R(0) line of CO perturbed by Ar is studied experimentally in a wide pressure range. Line shape parameters are calculated ab initio using two potential energy surfaces for a wide temperature range. Theoretical model reproduces experimental spectra at a sub percent level of uncertainty. Significance of the line-mixing effect for accurate modeling of spectra is demonstrated. Abstract: We use three independent spectroscopic techniques, operating in the millimeter-wavelength range, to study molecule-atom collisions, and validate our quantum-scattering calculations on two recent potential energy surfaces. We study the first pure rotational transition in a CO molecule perturbed by Ar. This molecular system is a good prototype of atmospherically relevant cases. It is, on the one hand, affordable for calculation of the line shape parameters by modern ab initio methods, and on the other hand, is very convenient for experimental studies because of its regular, well spaced rotational spectrum having a moderate intensity. We show that the simulated collision-perturbed spectra, which are based on our fully ab initio calculations, agree with the experimental line profiles at sub-percent level over a wide range (more than four orders of magnitude) of pressures. We demonstrate that the agreement between theory and experiment can be further improved if the model accounts for the collisional transfer of an optical coherence between different rotational transitions (the line-mixing effect). We show that the two surfaces tested in this work lead to a very similar agreement with the experiment. Capability of calculating line shape parameters in a broad range of temperatures is demonstrated.